2015
DOI: 10.1007/s40261-015-0366-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Henagliflozin, a Sodium Glucose Co-Transporter 2 Inhibitor, in Chinese Patients with Type 2 Diabetes Mellitus

Abstract: The observed pharmacokinetic and pharmacodynamic profiles of henagliflozin support a once-daily dosing regimen in Chinese T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Henagliflozin (SHR3824) is a novel, highly selective, oral inhibitor of SGLT2 12,13 . Our previous phase 2 trial (NCT02366351) showed that 12‐week treatment of henagliflozin monotherapy provided efficacious glycaemic control, reduced body weight and blood pressure, and was generally well tolerated in Chinese patients with T2D and inadequate glycaemic control with diet and exercise (data submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Henagliflozin (SHR3824) is a novel, highly selective, oral inhibitor of SGLT2 12,13 . Our previous phase 2 trial (NCT02366351) showed that 12‐week treatment of henagliflozin monotherapy provided efficacious glycaemic control, reduced body weight and blood pressure, and was generally well tolerated in Chinese patients with T2D and inadequate glycaemic control with diet and exercise (data submitted for publication).…”
Section: Introductionmentioning
confidence: 99%
“…3,11 Henagliflozin (SHR3824) is a novel, highly selective, oral inhibitor of SGLT2. 12,13 Our previous phase 2 trial (NCT02366351) showed that 12-week treatment of henagliflozin monotherapy provided efficacious glycaemic control, reduced body weight and blood pressure, and was generally well tolerated in Chinese patients with T2D and inadequate glycaemic control with diet and exercise (data submitted for publication). Herein, we conducted a phase 3 trial to further evaluate the efficacy and safety of henagliflozin monotherapy in this population, with results from the 24-week placebo-controlled period and additional 28-week extension period reported.…”
Section: Introductionmentioning
confidence: 99%
“…inhibitor reduced plasma glucose level in a dose-dependent manner. No severe side effects were reported for this small group of T2DM patients with doses ranging from 5 -20 mg per day [67].…”
Section: Henagliflozinmentioning
confidence: 72%
“…The authors suggested that henagliflozin is suitable for, once daily, regimen [67]. 12 weeks, lowers postprandial glucose spike, and weight.…”
Section: Henagliflozinmentioning
confidence: 99%
“…Henagliflozin exhibited dose-proportional PK properties in both T2DM patients and healthy volunteers. 7 It can be rapidly absorbed after single-dose oral administration, with a T max of 1.5-3 h and a half-life ranging from 11 to 15 h. 8 Glimepiride, with a better safety profile than the firstgeneration sulfonylureas and prolonged action duration, is one of the most widely used sulfonylureas in the treatment of T2DM. 9 It is used as a second-line drug in conjunction with metformin or insulin 10,11 or as monotherapy used in patients who are intolerable to metformin.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%